Introducing the medieval swan. - Goodison, Natalie Jayne (University of Wales Press, 2022)
This book examines the swan in medieval literature, spanning from Classical to Early Modern associations.
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism.; Swans in literature.; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; HISTORY / Europe / Medieval; English literature -- Middle English; Swans in literature; 1100-1500; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.